Strengthening women's empowerment and inclusion in the Living Lab for People (LL4P) in Kenya and Colombia - Ewell, Hanna; Vanegas, Martha; Mwambi, Diana; Omondi, David; Rietveld, Anne (2024)
The team examined the intersections of women’s empowerment, climate resilience, and agricultural innovation in the context of a Living Lab for People (LL4P) approach in Kenya and Colombia. Utilizing the project-level Women’s Empowerment in Agriculture Index (pro-WEAI) survey in Kenya and qualitative methods in both countries, this research highlights the critical role of gender-responsive strategies in fostering climate resilience within rural communities. The study’s findings emphasize that women often lack decision-making power and access to resources in agricultural production, with men typically controlling production-related decisions. Despite these constraints, women are actively involved in areas like poultry management and informal dairy marketing. Limited financial resources, market access, and climate information present significant barriers to women’s ability to implement transformative agricultural practices. However, collective initiatives and locally adapted practices indicate growing community resilience. The LL4P model is promising for integrating women’s perspectives and creating pathways for gender equality within low-emission, climate-resilient food systems. The report concludes that expanding support for training, resources, and gender-equitable decision-making structures will be essential for sustainable agricultural development. These insights aim to inform future LL4P initiatives, contributing to the broader agenda on gender-responsive climate-smart agriculture.